How Women IAS Officers in Kerala cop with their work - K. A, Shoyab. (International Journal of Psychosocial Rehabilitation, 2020)
Public administration is an obvious part of the government, and this study refers to the women in higher public administration of Kerala state. Though Kerala has acquired 100 percent literacy, the representation of women in this area is very poor, but once they reach this position, they can achieve top positions and act very powerful, ideal, and pragmatic. This article is written based on the primary data collected through a semi-structured interview with the lady IAS officers in the Kerala state. They revealed their emotions and experiences and how they related to their family and workplace.